A case report of primary colonic paraganglioma with lymph node metastasis - Zhu, Xinyi; Huang, Zhen; Dong, Lin; Zhao, Hong; Lu, Haizhen (Frontiers in Surgery, 2022)
Abstract Background: Paraganglioma is a kind of neuroendocrine tumor that originates from paraganglia outside the adrenal gland. Gastrointestinal tract paraganglioma is very rare and only four cases of paraganglioma originating in the colon have been reported. Case Presentation: We report a case of metastatic paraganglioma originating in the colon, in which the differential diagnosis was established by comprehensively considering clinical information, histology, immunohistochemistry, and findings of fluorescence in situ hybridization and next generation sequencing analyses. The patient has remained well for over 14 months after the treatment. Conclusion: Since all paraganglioma have metastatic potential, we believe that radical surgical resection and regular follow-up are necessary. Genetic testing may be indicative of metastatic potential and prognosis. Because colonic paraganglioma is very rare, differential diagnosis is very important. Our report provides experience for the diagnosis and study of paraganglioma in rare sites.